Visceral fat area is an independent predictive biomarker of outcome after first-line bevacizumab-based treatment in metastatic colorectal cancer. Issue 3 (15th October 2009) - Guiu, Boris; Petit, Jean Michel; Bonnetain, Franck; Ladoire, Sylvain; Guiu, Séverine; Cercueil, Jean-Pierre; Krausé, Denis; Hillon, Patrick; Borg, Christophe; Chauffert, Bruno; Ghiringhelli, François
Abstract : Background: Adipose tissue releases angiogenic factors that may promote tumour growth. Objective: To determine whether body mass index (BMI), subcutaneous fat area (SFA) and visceral fat area (VFA) are associated with outcomes in patients given first-line bevacizumab-based treatment for metastatic colorectal cancer (MCC). Patients: CT was used to measure SFA and VFA in 120 patients with MCC who received bevacizumab-based treatment (bevacizumab group, n=80) or chemotherapy alone (chemotherapy group, n=40) as first-line treatment. Associations linking BMI, SFA and VFA to tumour response, time-to-progression (TTP) and overall survival (OS) were evaluated. Results: In the bevacizumab group, median follow-up lasted for 24 months (3–70). BMI, SFA and VFA values above the median (ie, high BMI, high VFA and high SFA) were significantly associated with absence of a response. TTP was shorter in patients with high BMI (9 vs 12 months; p=0.01) or high VFA (9 vs 14 months; p=0.0008). High VFA was associated with shorter OS (p=0.0493). By multivariate analysis, high VFA was independently associated with response, TTP and OS (HR=7.18, p=0.008, HR=5.79, p = 0.005 and HR=2.88, p = 0.027, respectively). In the chemotherapy group, median follow-up lasted for 30 months (4–84). BMI, SFA and VFA were not associated with response, TTP or OS. In the whole population, interaction between VFA and bevacizumab administration was significant for response (OR=3.31, p=0.005) and TTP (HR=1.64, p=0.022), thereby confirming the results. Conclusion: This study provides the first evidence that high VFA independently predicts a poorer outcome in patients given first-line bevacizumab-based treatment for MCC. However, this predictive biomarker needs to be validated in a different dataset.